Is TSH a Reliable Indicator of Thyroid Hormone Status in Pregnancy? - Karavani, Gilad; Daoud-Sabag, Lina; Chay, Cherut; Gillis, David; Strich, David (Hormone and Metabolic Research, 2022)
Thyroid screening is recommended during pregnancy with serum thyrotropin (TSH) as the primary test. However, since human chorionic gonadotropin, the serum hallmark of pregnancy, has TSH-like effects, the adequacy of TSH as a screening tool in this constellation requires further study. This study aimed to evaluate the relationship between TSH and thyroid hormones during pregnancy in order to determine if TSH is an adequate screening tool. This was a retrospective study utilizing the Clalit Health Service, Jerusalem district database between 2006–2017 in which we analyzed TSH, FT4 and FT3 measurements from 32430 pregnancies resulting in live birth. We grouped FT4 and FT3 levels by trimester and by the following TSH levels: (1) below 0.1/0.2/0.3 mIU/l, (2) 0.1–2.5/0.2–3.0/0.3–3.0 mIU/l, (3) 2.6–4.0/3.1–4.0 mIU/l, (4) 4.1–10.0 mIU/l and (5) above 10.0 mIU/l. In the first trimester, the most important for fetal brain development, FT3 was below normal, defined as below the 2.5th percentile for the population, in only 15.3% of tests with TSH over 10 mIU/l. FT4 was below normal in only 12.8% of such tests. Similar findings were noted for the second and third trimesters. As expected, there were far less abnormal tests when lower TSH cutoff levels were tested. In conclusion, TSH levels beyond the range accepted as normal do not, in most cases, reflect abnormal thyroid hormone levels during pregnancy. TSH is not a good screen for overt hypothyroidism in pregnancy. This may be due, at least in the first trimester, to thyrotropic effects of HCG.